2016
DOI: 10.1097/tp.0000000000000976
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thymoglobulin by Stem Cell Source (Peripheral Blood Stem Cell or Bone Marrow) After Myeloablative Stem Cell Transplantation From HLA 10/10-Matched Unrelated Donors

Abstract: Although our results confirm the recommendation for ATG to be added after PBSC transplantation, no obvious benefit was identified using this approach in the setting of BM transplantation. Only prospective studies may yield definitive answers to this question.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…On the other hand, Ravinet et al reported no significant impact of ATG in MUD BMSC. In this study various total doses of ATG were used at the discretion of the attending physician (range <5 ->10 mg/kg, only 10 patients received ATG less than 5 mg/kg) (38). In both studies Thymoglobuline was used, as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Ravinet et al reported no significant impact of ATG in MUD BMSC. In this study various total doses of ATG were used at the discretion of the attending physician (range <5 ->10 mg/kg, only 10 patients received ATG less than 5 mg/kg) (38). In both studies Thymoglobuline was used, as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, two recent studies revealed a greater benefit of ATG in PBSCT than in BMT [38,44]. An explanation for this finding may be the higher burden of severe cGVHD following PBSCT compared to BMT in case of T cell-replete, ATG-free transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding ATG, Ravinet et al [55] reported that the addition of ATG after a MAC regimen in patients with acute leukemia and MDS transplanted from a well-matched unrelated donor (10/10) was found to significantly reduce aGvHD and cGvHD, and improve graft-versus-host disease-free, relapse-free survival only after PBSC but not after BM transplantation. Survival, relapse, or NRM were not affected by ATG administration.…”
Section: Summary Of Evidencementioning
confidence: 99%